PEMBANGUNAN RUMAH IBADAT DI KOTA MEDAN DALAM KONTEKS PERIZINAN (Studi Terhadap Peraturan Bersama Menteri Agama dan Menteri Dalam Negeri Nomor 9 dan Nomor 8 Tahun 2006 Tentang Izin Pembangunan Rumah Ibadat) - Roni Eko Wisuda Rambe; Jusmadi Sikumbang; Mirza Nasution; Suhaidi Suhaidi (USU LAW JOURNAL, 2016)
ABSTRACT   Legal substances establishment of houses of worship in the city of Medan is divided in three components namely the structural components of the law in this cases in the conceptual framework of the applicable rule and regulations regarding the licensing houses of worship, namely construction of 1945; Law No. 28 of 2002 on building regulations, along religious affairs minister and minister of interior number 9 and 8 of 2006 on the establishment houses of worship; towns and local regulations number 5 2012 concerning the levy of building permits. Component substance of the law, namely the legal entities related of governance of licensing house of worship in the city of Medan that the city administration of Medan, the ministry of religion and forum religious harmony city of Medan, department of spatial and urban planning, as well as the official licensing of integrated city of Medan, further substance component of the legal culture in this case is the implementations of such rules in a society that must be adapted to the system of values, norm and habits in urban terrain to run properly and effectively. Keywords  : Houses of Worship, Licensing, Legal Effectiveness